Sandwichworkz : the fusion street café - Roy, Debjit; Raut, Mukund; Agrawal, Sanchit; Agrawal, Shubham (London : Indian Institute of Management, Ahmedabad, 2018)
Takshshila, the owner of Sandwichworkz, a hip and trendy restaurant in Ahmedabad, India is worried about the dipping profitability of the restaurant. To get a hold on the decreasing profitability, she knew she had to optimize her menu and change it, if need be. Takshshila hired Nick, a restaurant consultant to identify the cost of making each menu item and identify further problem areas using a menu-engineering tool. However, Nick has come across a new costing methodology and wonders whether his method of cost calculation was optimum or not. Since the new costing methodology has not gathered universal acceptance, should Nick stick to his method of costing or adopt the new methodology? Would the new methodology affect his recommendations? Should Takshshila and Nick get involved in capturing the extra data required to calculate menu item costs through this new methodology?
Originally Published InRoy, D., Raut, M., Agrawal, S., & Agrawal, S. (2018). Sandwichworkz – The Fusion Street Café. PROD0316. Ahmedabad, India: Indian Institute of Management, Ahmedabad.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sandwichworkz -- Case studies; Restaurant management -- India -- Case studies; Cost accounting -- India -- Case studies